I‐sharing across the aisle: Can shared subjective experience bridge the political divide?. Issue 6 (9th March 2022) - Pinel, Elizabeth C.; Fuchs, Natalie A.; Benjamin, Shania
Abstract: The U.S. witnessed deep ideological rifts during the 2020 presidential election, with reverberations that continue to this day. Both the media reports and the research evidence reveal the passion with which people cling to their ideologies and the barriers to communication that people often erect between themselves and those who do not share their political viewpoints. Consider the insurrection at the U.S. Capitol in January 6, 2021, as an historical example of the vilification and disrespect that people express toward those with different viewpoints from their own. Here we test whether moments of shared subjective experience (i.e., I‐sharing) can facilitate liking for politically different others, as well as more productive dialogue across political lines. Drawing from previous work on the intergroup implications of I‐sharing, we predicted and found that I‐sharing increased liking for one's interaction partner, irrespective of one's own political preferences and irrespective whether one's interaction partner shares those political preferences. In addition, I‐sharing (relative to not I‐sharing) promoted a greater sense among Biden supporters that they could have a productive dialogue with Trump supporters, although the parallel effect did not hold true for Trump supporters. The results point to the possibility that moments of I‐sharing can get people with differing political views to, as Biden put it so simply on November seventh, 2020, "listen to each other again."